Cone beam computed tomography findings in temporomandibular joint of chronic qat chewers: Dimensional and osteoarthritic changes - Almashraqi, Abeer A.; Halboub, Esam S.; Al-Maweri, Sadeq A.; Barngkgei, Imad; Al-Wesabi, Mohammed A.; Al-Kamel, Ahlam; Alhammadi, Maged S.; Alamir, Abdulwahab H. (Wiley, 2020)
The social habit of chewing qat (also known as khat) is widely practised in East Africa and the Arabian Peninsula. It has been linked with various oro-facial conditions, including temporomandibular joint disorders (TMD). This cross-sectional, comparative study sought to investigate the effects of qat chewing on temporomandibular joint (TMJ), using cone beam computed tomography (CBCT). A total of 85 Yemeni males were included. The participants were divided into two groups: Qat chewers (QC; n = 41) and non-qat chewers (NQC; n = 44). Relevant data were obtained using a structured questionnaire and standardised clinical examination. Additionally, CBCT images of the TMJs were obtained, and then, osteoarthritic changes and TMJ dimensions were analysed. SPSS 21 was used for statistical analyses, with a significant level was set at 0.05. Compared to NQC, a significantly higher proportion of QC presented with clinical signs of TMDs. The qualitative CBCT findings revealed significantly higher osteoarthritic changes in QC than in NQC: osteophyte (51.2% vs 22.7%; P = .008), subcortical sclerosis (48.8% vs 27.3%; P = .047), articular surface flattening (46.3% vs 6.8%; P = .009) and subcortical cysts (43.9% vs 4.5%; P < .001). However, CBCT quantitative findings (condylar dimensions) did not show significant differences between the two groups. The chewing side of the QC group showed slightly more changes compared to the non-chewing side. The results demonstrate that qat chewing has detrimental effects on TMJ manifested mainly as osteoarthritic changes. Further large-scale studies are recommended.